Cold dwell fatigue of titanium - Xiong, Y (2021)
There is a long-standing technological problem in which a stress dwell during cyclic loading at room temperature in Ti causes a drastic fatigue life reduction. It is thought that localised time dependent plasticity in ‘soft’ grains oriented for easy plastic slip leads to load shedding and an increase in stress within a neighbouring ‘hard’ grain that is poorly oriented for easy slip. Quantifying this time dependent plasticity process is key to successfully predicting the complex cold dwell fatigue problem. Incorporating the influence of operating temperatures and common alloying elements on cold dwell fatigue will be beneficial for future alloy design to address this problem.